Precursors to probation and parole agent intent to send informational, emotional, and esteem social support messages to female clients. Issue 3 (4th May 2019) - Smith, Sandi W.; Morash, Merry; Walling, Brandon; Adams, Elizabeth A.; Holmstrom, Amanda J.
ABSTRACT: Supervising agents serve as sources of social support for over one million women in the US on probation and parole who strive to avoid recidivism. Little is known about the supportive messages agents intend to provide their female clients or their precursors. The optimal matching model of social support is used in an investigation of the precursors to agents' intent to send different types of social support messages to the women they supervise. Results indicated that supervising agents intended to provide informational support in the form of suggestions or advice, esteem support in the form of compliments, and emotional support in the form of encouragement to the women. Both agent communication pattern and offender level variables were precursors to the intent to send informational support messages, but only agent communication pattern variables predicted the intent to send emotional support messages.